Advances in Chondroitin Sulfate-Based Nanoplatforms for Biomedical Applications - Peng C; Zheng A; Wang L; Shen Y; Peng C; Yu J; Shao S (International Journal of Nanomedicine)
Cunming Peng,1,* Anna Zheng,1,* Liangliang Wang,2 Yingjie Shen,1 Changchun Peng,3 Jingmou Yu,1,4 Shengwen Shao1,4 1Zhejiang Provincial Key Laboratory of Vector Biology and Pathogen Control, Huzhou University, Huzhou, 313000, People’s Republic of China; 2Affiliated Hospital of Jiujiang University, Jiujiang, 332000, People’s Republic of China; 3Jiangxi Jimin Kexin Pharmaceutical Co., Ltd., Yichun, 332000, People’s Republic of China; 4Jiangxi Provincial Key Laboratory of Cell Precision Therapy, School of Basic Medical Sciences, Jiujiang University, Jiujiang, 332005, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jingmou Yu, Email yjm1016@hotmail.com Shengwen Shao, Email shashe98@163.comAbstract: Chondroitin sulfate (CS) is a naturally sulfated glycosaminoglycan with diverse biofunctional properties, including anti-inflammatory effects, reactive oxygen species scavenging, cartilage regeneration and immune regulation. In recent years, CS has shown significant progress in biomedical applications, particularly in drug delivery, tissue engineering, and biosensing. This paper reviews the latest advancements of CS-based nanoplatforms in the biomedical field. CS can be integrated with functional molecules to construct a variety of nanostructures, further expanding its potential applications. CS exhibits distinctive characteristics, and CS-based nanoparticles could serve as promising drug delivery vehicles in tumor therapy. Beyond their roles in drug delivery, CS-based nanoplatforms exhibit transformative potential in tissue engineering, offering promising solutions for wound repair and tissue regeneration. Additionally, CS enhances early disease diagnostics through biomarker detection, leveraging its unique molecular structure and biocompatibility. This comprehensive review explored the properties of CS-based nanoplatforms and their diverse applications, aiming to provide a reference for related research and encourage further advancements in the biomedical fields. Keywords: chondroitin sulfate, nanoplatforms, tumor therapy, tissue engineering, biological sensing